Yield and Moisture Use Pattern of Rabi Crops Grown Under Rainfed Conditions of Eastern U.P. - Singh, R A; Singh, O P; Sharma, H C; Singh, Mahatim (Annals of Arid Zone, 2016)
Wheat, barley, gram and linseed were grown under rainfed conditions on the Research farm of Banaras Hindu University during the rabi seasons of 1971 to 1974. Gram and barley were found to be superior to wheat and linseed for grain production. Linseed was the poorest in grain production. Total moisture use of gram was highest followed by barley, wheat and linseed. Wheat variety Kalyan sona and C 306, barley variety DL 3 and Ratna, gram variety T I and 3 and linseed variety T 397 were promising varieties in respect of moisture use efficiency.